Design factors contributing to active urban squares in Malaysia - Zakariya, Khalilah; Harun, Nor Zalina; Mansor, Mazlina (American Scientific Publishers, 2017)
Urban squares are a type of public open space that cater for various activities for the public. While the design of urban squares has been studied in depth by researchers in other countries, however, local studies that interrogate how urban squares are occupied in Malaysia are still scarce. Due to the lack of documentation on the fundamental design criteria of urban squares that suit the local and socio-cultural needs, some squares are not strategically located and poorly designed, which eventually make them inactive. This research examined three prominent urban squares, which are Dataran Putra, Dataran Merdeka and Dataran Pahlawan, to explore and outline the design factors that contribute to the activities of the squares. The methods adopted for this research comprised of conducting site inventory and photographic documentation, observation and mapping, and semi-structured interviews with 150 visitors. The analysis revealed that there are two additional design factors that contribute to active urban squares, which are, (i) the combination of hard-paved area and open lawn, and (ii) combination of shaded and non-shaded areas. The findings from this research are useful for Landscape Architects and Urban Designers in planning and designing urban squares in Malaysia, or upgrading underutilized urban squares. This research concluded that the activities of urban squares are contributed by common design factors as any other public spaces, and, localized design factors such as the local climate and local lifestyle.